Formação de gestores públicos na Rede Federal de Educação Profissional, Científica e Tecnológica: um estudo sobre o desenvolvimento de competências gerenciais - JESUS, Kelly Cristina Brito de (2014)
Competent public managers are strategic actors to implement principles and practices of the managerialist reform in Brazil. In this perspective, the defense of competent public managers to manage has become an emerging issue on the process of transformation that the reformist agenda had proposed. The objective of this research is to analyze how public managers develop management competencies. It was adopted in this research a quantitative methodology, involving 110 public managers of Federal Educational Institutions - IFEs. In order to comply with the quantitative methodology, two scales were built - Scale of organizational learning modalities and Scale of managerial competencies. The scales were validated from exploratory factorial analysis and to identify the relationship among the variables, the multiple regression analysis was performed. The results indicate that the cognitive functional management skills are explained by the modalities of reading texts/database and mentoring skills and behavioral management skills policies are more influenced by the modes of reading texts/database and communities of practice. The results also suggest that public managers develop skills by using learning methods that approximate more cognitive assumptions and, with less relevance, through participative and practice-based processes.